Bosnia and Herzegovina : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bosnia and Herzegovina. (IMF Staff Country Reports; Country Report ;, 2022)
Bosnia and Herzegovina (BiH) is facing considerable challenges just as it has rebounded from the Covid-19 pandemic. Spillovers from the war in Ukraine are fueling inflation and weighing on domestic spending and external demand, while domestic political tensions are hampering economic policies and reforms.